Cancer-associated fibroblasts: heterogeneity, tumorigenicity and therapeutic targets - Keke Lv; Tianlin He (Molecular Biomedicine)
Abstract Cancer, characterized by its immune evasion, active metabolism, and heightened proliferation, comprises both stroma and cells. Although the research has always focused on parenchymal cells, the non-parenchymal components must not be overlooked. Targeting cancer parenchymal cells has proven to be a formidable challenge, yielding limited success on a broad scale. The tumor microenvironment(TME), a critical niche for cancer cell survival, presents a novel way for cancer treatment. Cancer-associated fibroblast (CAF), as a main component of TME, is a dynamically evolving, dual-functioning stromal cell. Furthermore, their biological activities span the entire spectrum of tumor development, metastasis, drug resistance, and prognosis. A thorough understanding of CAFs functions and therapeutic advances holds significant clinical implications. In this review, we underscore the heterogeneity of CAFs by elaborating on their origins, types and function. Most importantly, by elucidating the direct or indirect crosstalk between CAFs and immune cells, the extracellular matrix, and cancer cells, we emphasize the tumorigenicity of CAFs in cancer. Finally, we highlight the challenges encountered in the exploration of CAFs and list targeted therapies for CAF, which have implications for clinical treatment.